Management of abiotic stress in grapes (Vitis vinifera) - a review - Somkuwar , R.G.; Waghmare, G.M.; Gharate, P S; Gobade, N. J.; Thutte, A.S.; Ausari, P.K. (Current Horticulture, 2025)
Since viticulture is highly dependent on weather and climate, several climate change projections have been generated with the expectation that they may worsen the distribution of grape-growing regions in the years to come. Abiotic stress factors such as drought, salinity, temperature, hailstorm, and rainfall can restrict the growth and productivity of grapevines, as well as affect their quality and composition. Especially during critical developmental stages such as flowering, fruit set and ripening. This paper focused on review of current knowledge available on the effects of these stressors on grapevine physiology, development, and yield as well as the strategies and techniques to mitigate them. The paper provides a comprehensive overview of the management of abiotic stress in grapes and the challenges and opportunities for future research and grape growers can minimize the negative impacts of abiotic stresses.